Picturing atrocity : photography in crisis - Batchen, Geoffrey (London : Reaktion, 2012)
- Machine generated contents note: Introduction / Joy Prosser##- Words Can Kill: Haiti and the Vocabulary of Disaster / Rebecca Solnit##- Visible and Invisible Scars of Wounded Knee / Mick Gidley##- Severed Hands: Authenticating Atrocity in the Congo, 1904-13 / Christina Twomey##- Atrocity and Action: The Performative Force of the Abu Ghraib Photographs / Peggy Phelan##- Photographing Atrocity: Becoming Iconic? / Griselda Pollock##- The Iconography of Famine / David Campbell##- A Single Image of Famine in China / D.J. Clark##- History at a Standstill: Agency and Gender in the Image of Civil Rights / Elisabeth Abel##- Body on a Hillside / Susan Meiselas##- Crossfire / Shahidul Alam##- The Iconic Image of the Mushroom Cloud and the Cold War Nuclear Optic / Robert Hariman / John Louis Lucaites##- The Girl in the Photograph: The Visual Legacies of War / Nancy K. Miller##- Atrocity, the "As If," and Impending Death from the Khmer Rouge / Barbie Zelizer##- The Falling Man / Tom Junod##- Contents note continued: Street Photographs in Crisis: Cernauti, Romania, c. 1943 / Marianne Hirsch / Leo Spitzer##- Picturing the Perpetrator / Paul Lowe##- War Trophy Photographs: Proof or Pornography? / Hilary Roberts##- Picturing an "Ordinary Atrocity": The Sharpeville Massacre / Darren Newbury##- Looking Askance / Geoffrey Batchen##- Documentary Pictorial: Luc Delahaye's Taliban, 2001 / Mark Durden##- The Execution Portrait / Ariella Azoulay##- Toward a Hyperphotography / Fred Ritchin##- Lament of the Images / David Levi Strauss / Alfredo Jaar##- Photographic Interference / Lorie Novak.
boek